Aquisição de linguagem nas especificidades da encefalopatia crônica não progressiva: uma abordagem multimodal - Polia, Andreza Aparecida (2019)
The objective of this thesis is to identify and describe how the process of development of multimodal language in children with non-progressive chronic encephalopathy (NPCE) occurs, based on family relationships, especially the mother-child dyad in scenes of joint attention. NPCE affects the developing brain resulting in permanent motor sequelae besides possible speech, vision and hearing alterations that directly impact on the language acquisition process. In order to approach the linguistic characteristics of the NPCE, we discuss Sanclemente (2001) and Lamônica (2014; 2015), for interlocution on joint attention, we adopt Tomasello (2003) and Costa Filho (2015), for gestural production, we rely on McNeill (1985;1992;2000), for children's oral productions, on Barros (2012) and, with regard to multimodality in the process of language acquisition, on Cavalcante (1994, 1999, 2010, 2015), Fonte (2011) and Avila-Nóbrega (2010; 2017). This is a case study associated with the Laboratory of Speech and Writing Acquisition of the Federal University of Paraíba. The subjects of the study were two children diagnosed with NPCE, a girl with spastic quadriplegic, attended from age 15 to 27 months-old in interactions with her female genitor (Dyad A) and also with her grandmother; and a boy with spastic triparesis, attended from age 16 to 28 months-old also in interaction with his mother (Dyad B) and his sister. During 12 months, filming was done biweekly in naturalistic situations, and afterwards transcribed and analyzed through ELAN software that allows visualizing the occurrence of multimodal elements. A journal at each meeting was also produced, containing the description of the scenes and records of the most significant aspects of the interactions between the participants. Qualitative data analysis emphasizes the child of the dyad B was able to produce gesticulation, pantomimes and emblems, along with the use of babbling at the beginning of the research, and holophrases, words and blocks of statement at the end, besides making use mainly of the conventional pointing and gazing to guide and sustain the attention of the partners and initiate the scenes of joint attention. The child of the dyad A managed to gesture and make use of emblems when imitating the partners. Moreover, she communicated through babbling and a few words, but the ocular movement was the main way of expression used to initiate and sustain the attention of her interlocutors in the interactions. In the quantitative aspect, during the 12-month period the child of the dyad A increased the frequency of vocalizations which were observed combined with body movements, gesturing or gestures, and always guided by eye movements. The child of the dyad B started using blocks of statements and increased the frequency of the use of the pointing gesture. Specifically in the dyad B, it was possible to observe the child uses the same linguistic and gestural behavior of his female genitor which can be categorized as more directive than dialogical, as opposed to the behavior of the dyad A. To both children, the use of the gaze was the main communication strategy used to show partners some event, and / or to initiate and sustain a dyadic, triadic or quadratic interaction. This study may contribute to children's interactions in different contexts, helping participants in their daily lives to understand ocular cues, oral productions and gestures, without letting the social representation of the pathology deprive them of learning opportunities inside and outside the school environment.